A kolozsvári egyetemen oktatott "Nemzeti irodalmak" fogalmainak versengése az 1870-es években - Nagy Zabán, Márta (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
In this paper, through the example of the Hungarian and Romanian language and literature department of the Hungarian Royal University of Kolozsvár I have attempted to analyze that the establishment of the university in Kolozsvár at a certain point of the history of professionalization was not organized according to the logic of evolution history, its tendency of forming cannot be described as a progress from a less professionalized state to an increasingly professionalized and specialized state, in fact, by inheriting several elements from the structures of the earlier phases of the history of professionalization it elaborated its administrative framework according to the local special circumstances and to the requirements and decisions set out by Budapest, and defined its premises of scientific ideology.